RADARSAT: The Antarctic Mapping Project. Proceedings of the Science Objectives and Requirements Meeting - Jezek, Kenneth C.; Carsey, Frank D. (Byrd Polar Research Center, The Ohio State University, 1993)
On March 30, 1993 a meeting was convened at the Byrd Polar Research Center of The Ohio State University to discuss plans for the complete imaging of Antarctica with the synthetic aperture radar to be carried aboard the Canadian RADARSAT. Some 30 scientists from the U.S. and Canada participated in the meeting. The purpose of the meeting was to develop science objectives for the project, and identify science requirements for acquiring, reducing and distributing data from the planned two mapping periods. This report summarizes the outcome of the science meeting. Participants were briefed on potential science applications of RADARSAT data based on experience gained with the first European Remote Sensing Satellite (ERS-l). An in depth review of RADARSAT system attributes was also presented. NASA Office of Polar Programs, National Science Foundation Canadian Space Agency